PENGGUNAAN KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM Studi Kasus di SMP Negeri 7 Sambas Tahun Ajaran 2025/2026 - Safika Safika; Oskar Hutagaluh; Bayu Bayu (ADIBA : JOURNAL OF EDUCATION, 2025)
The purpose of this study is to analyze the experiences of Islamic Religious Education (IRE) teachers in utilizing Artificial Intelligence (AI) to support the learning process at SMP Negeri 7 Sambas, to describe the forms of its implementation, and to identify the benefits and challenges faced by teachers in its application.This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation. The data analysis used Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. To ensure data validity, this study applied source triangulation and member checking techniques.The results of the study indicate that IRE teachers at SMP Negeri 7 Sambas have positive experiences in using various AI applications such as ChatGPT, Quizizz AI, and Google Form AI Plugin, as these tools are considered helpful in enriching learning materials, simplifying test preparation, and enhancing students’ learning motivation.The implementation of AI in IRE learning includes the development of digital materials, creation of interactive assessments, online-based evaluations, and enrichment of teaching content through digital platforms.However, teachers also encountered several challenges, including limited technological skills, lack of training, inadequate school infrastructure, and concerns over reduced quality of spiritual interaction and personal guidance between teachers and students.This study concludes that the use of AI by IRE teachers has great potential to improve the quality of learning, provided that continuous training, adequate infrastructure, and integration of Islamic values are ensured so that technological use remains aligned with the goals of Islamic Religious Education.